A comparative study of the environmental impact of alkali activated and traditional materials - Pavia, Sara (My University, 2022)
Many construction materials carry significant environmental impacts because they require high energy input and non-renewable materials for production, contributing to material depletion and greenhouse gas emissions. In particular, Portland cement (PC), the binder most widely used, is often considered a main contributor to emissions. Most PC environmental impact is due to clinker production which requires burning rocks at 14000C releasing abundant CO2 from fuel combustion and rock decarbonization. Alkali-activated materials (AAMs) do not require clinker manufacturing but are produced at low temperature (ambient-100◦C). Hence, they yield low emissions and have low embodied energy (EE). Most AAMs are made with waste which further lowers their EE and the raw materials and fuel consumption for their making. Savings up to 75% CO2 emissions are reported compared with PC products, and additional environmental benefits (water consumption reduction and no requirement for superplasticizers). This paper calculates the EE and carbon footprint (EC) of AAMs made with wastes including slag (GGBS), fly ash (FA), bauxite and red mud (RM). The values are compared with equivalent CEM II products. Their environmental impact is set against their strength to assist the design of optimum mixes at lower impact. It is evidenced that the right activator procures a strength similar to CEM II at approximately half the EE and EC, while a wrong activator increases the environmental impact and lowers strength. Pyroprocessing waste at relatively low temperature slightly increases environmental impact but can greatly increase strength: sintering bauxite at 8000C enabled strength two times greater than the CEM II product.
Civil Eng. Research Ireland
Keywords: Carbon footprint; Fly ash; GGBS; Red mud; Bauxite; Alkali activation; Embodied energy; Nanoscience & Materials; Smart & Sustainable Planet; low carbon materials